STRATEGI RRI.CO.ID YOGYAKARTA DALAM UPAYA MEMBANGUN CITRA POSITIF DI YOGYAKARTA DI TENGAH ISU KLITIH - Bima Kramawijaya; Zahrotus Sa'idah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
This research analyzes the agenda-setting strategies employed by the news portal rri.co.id in building a positive image of Yogyakarta City regarding the phenomenon of "klitih." Through interviews with rri.co.id editors and journalists and an analysis of published news articles, the study reveals that rri.co.id utilizes an agenda-setting strategy by reframing the term "klitih" as "street crimes" in their reporting. This strategy aims to alleviate the perceived tension among the public and construct a positive image of Yogyakarta City. Furthermore, the research highlights the crucial role of journalists and editors in crafting accurate and responsible news content. The findings align with the agenda-setting theory, which elucidates how the media influences public attention and policymaking through agenda setting. This research provides a better understanding of the media's influence in shaping regional images and the contribution of agenda-setting strategies in the 'klitih' issue in Yogyakarta.